Lessons from randomised controlled trials of continuous positive airways pressure therapy in the prevention of cardiovascular morbidity and mortality - Gildeh, Nadia; Rosenzweig, Ivana; Kent, Brian D. (Journal of Thoracic Disease, 2017)
Obstructive sleep apnoea (OSA) has an established independent relationship with cardiovascular disease, with a multitude of clinical cohort and longitudinal population studies showing a significantly increased risk of cardiovascular morbidity and mortality in subjects with severe OSA (1-3).